Biomaterials for Sequestration of Growth Factors and Modulation of Cell Behavior. (12th March 2020) - Teixeira, Simão P. B.; Domingues, Rui M. A.; Shevchuk, Mariya; Gomes, Manuela E.; Peppas, Nicholas A.; Reis, Rui L.
Abstract: Growth factors (GFs) are proteins secreted by cells that regulate a variety of biological processes. Although they have long been proposed as potent therapeutic agents, their administration in a soluble form has proven costly and ineffective due to their short half‐lives in biological environments. Biomaterial‐based approaches are increasingly sought as alternatives to improve the efficacy or, ideally, replace the need for exogenous administration of GFs in regenerative medicine strategies. The means by which these systems evolve from biomaterials for conventional controlled release of GFs to the recent extracellular matrix (ECM)–inspired approaches for sequestering these labile molecules and regulating their spatiotemporal activity and presentation are reviewed. Focus is placed on biomaterials functionalized either with ECM components, which show promiscuous GF binding, or with targeted GF ligands (antibodies, aptamers, or peptides). The potential of synthetic platforms with abiotic affinity as cost‐effective alternatives to the current biological ligands is also discussed. Overall, the various GF sequestering systems developed so far have remarkably improved the activity of GFs at reduced doses and, in some cases, completely avoided the need for their exogenous administration to guide cell fates. These bioinspired concepts thus enable the rational exploration of the full therapeutic potential of GFs in regenerative medicine. Abstract : Biomaterials for sequestration of growth factors are increasingly sought as alternatives to improve their efficacy or replace their exogenous administration in therapies. Recent extracellular matrix (ECM)‐inspired approaches, particularly functionalization with promiscuous ECM components or with targeted antibodies, aptamers, or peptides, are reviewed. Some of the most representative works are highlighted, and near future perspectives for the field are outlined.